Pelatihan Vacuum Frying untuk Produksi Keripik Jamur Tiram di Desa Tanjung Sangalang Pulang Pisau: Vacuum Frying Training for Oyster Mushroom Chips Production in Tanjung Sangalang Village, Pulang Pisau - Arifin, Samsul; Dirgantara, Made; Simbolon, Tiur Roida; Dony, Garry William (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The partner in this community service program is the Sangalang Hapakat Farmers Group located in Tanjung Sangalang Village, Kahayan Tengah District, Pulang Pisau Regency, Central Kalimantan. The current problem is the post-harvest processing of oyster mushrooms which is still carried out conventionally. Currently, the oyster mushroom chips production process is carried out using a frying pan so the product quality is not good and does not last long. In addition, the frying process also requires a lot of cooking oil consumption. The solution to this problem is to apply Vacuum Frying technology to the frying process and before packaging. This technology is an oil-saving frying system and the product results are tastier, so that the resulting product can last a long time (last up to 1 month). The method used in this community service uses the method of observing obstacles, solving problems, and analyzing needs as a follow-up to solving problems, then mentoring training on tools and testing the feasibility of tools, use, and maintenance of tools for Partners, as well as mentoring on packaging and product marketing.